KETERAMPILAN GURU PPKN DALAM MENERAPKAN MODEL PEMBELAJARAN PROBLEM BASED LERANING UNTUK MELATIH KEMAMPUAN PSIKOMOTORIK SISWA DI UPTD SMP NEGERI 5 KUPANG - Margerita Weni (SINERGI : Jurnal Riset Ilmiah, 2026)
The objective of this research is adjusted to the research problem,namely to determine the teacher’sskills in impementing the problem based learning model to develop students’psychomotor Abilities. The researcher used the method used in this research is a qualitative method.The data collection technique used in this research is observation, documentation and interview techniques.The data analysis used is descriptive analysis. The results of this study indicate that there is effectiveness of PPKn Teacher skills in Applying the problem based learning model to Train students’psychomotor Abilities.The application is in actively managing the class by providing relevant and challenging problems,guiding students actively without dominating,encouraging collaboration with clear roles in groups, and ensuring reflection and evaluation to deepen understanding.students towards real issues.